2006
DOI: 10.1093/jn/136.3.614
|View full text |Cite
|
Sign up to set email alerts
|

Virgin Olive Oil Phenols Inhibit Proliferation of Human Promyelocytic Leukemia Cells (HL60) by Inducing Apoptosis and Differentiation

Abstract: Although epidemiologic evidence and animal studies suggest that olive oil may prevent the onset of cancer, the components responsible for such an effect and their mechanisms of action remain largely unknown. In the present study, we investigated the effect of a virgin olive oil phenol extract (PE) on proliferation, the cell cycle distribution profile, apoptosis, and differentiation of the human promyelocytic cell line HL60. PE inhibited HL60 cell proliferation in a time- and concentration-dependent manner, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
110
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 42 publications
11
110
0
2
Order By: Relevance
“…The dialdehydic form of elenolic acid, linked to hydroxytyrosol or to tyrosol, has been shown to account, in part, for the antiproliferative and apoptotic effects of virgin olive oil phenol extract in human promyelocytic leukemia cells. 33 Strong antioxidant activity of 3,4-dihydroxyphenylethanol-elenolic acid was also reported. 26 The higher concentration of the linked forms of hydroxytyrosol and tyrosol present in our OVP extract 7 may account for the effects shown by OVP as compared with the isolated compounds studied.…”
Section: Discussionmentioning
confidence: 91%
“…The dialdehydic form of elenolic acid, linked to hydroxytyrosol or to tyrosol, has been shown to account, in part, for the antiproliferative and apoptotic effects of virgin olive oil phenol extract in human promyelocytic leukemia cells. 33 Strong antioxidant activity of 3,4-dihydroxyphenylethanol-elenolic acid was also reported. 26 The higher concentration of the linked forms of hydroxytyrosol and tyrosol present in our OVP extract 7 may account for the effects shown by OVP as compared with the isolated compounds studied.…”
Section: Discussionmentioning
confidence: 91%
“…Hydroxytyrosol (3, and tyrosol (p-HPEA) are the most representative olive oil phenols present both as free compounds and linked to the dialdehydic form of elenoic acid (3,4-DHPEA-EDA and p-HPEA-EDA) . Previous studies carried out in our laboratory have showed that these compounds exert a pro-apoptotic activity toward cancer cell lines (Fabiani et al 2002(Fabiani et al , 2006. In particular, we have found that 3,4-DHPEA at high concentrations (100µM) induces apoptosis on HL60 cells through an oxidative stress caused by the extracellular production of hydrogen peroxide (H 2 O 2 ) (Fabiani et al 2008).…”
Section: Introductionmentioning
confidence: 84%
“…3,4-DHPEA was obtained from Cayman Chemicals Ltd; protocatechuic, vanillic, ferulic, 3,4-dihydroxy-hydrocinnamic, o-coumaric and syringic acids were obtained from Fluka Co. (Buchs, Switzerland); gallic acid was from Carlo Erba (Milan) while oleuropein was purchased by Extrasynthese (Genay, France). 3,4 DHPEA-EDA and p-HPEA-EDA were purified by semi-preparative HPLC from a methanolic extract obtained from a virgin olive oil containing 650 mg/kg of total phenols as previously reported (Fabiani et al 2006). Tyrosol (p-HPEA) and all other reagents were purchased from Sigma-Aldrich (Irvine, UK) unless differently specified Cell treatment and apoptosis analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), which contained olive oil extracts, exhibit antioxidant activity [8] and apoptosis induction against colon cancer cells [9], and induce the differentiation of leukemia cells [10]. 4-Hydroxybenzyl alcohol (4HBA; 2) is a component of Gastrodia elata Blume (Orchidaceae) that has an anxiolytic-like effect on mice [11], and tyrosinase inhibitory activity [12].…”
Section: Introductionmentioning
confidence: 99%